KOMUNIKASI POLITIK KAMPANYE PEMILU DI INDONESIA 2024 PRESPEKTIF FILSAFAT BAHASA ANTONIO GRAMSCI - La Ilham Toha (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2024)
Abstract This article discusses the political communication strategy of the election campaign in Indonesia 2024 using the perspective of Antonio Gramsci's philosophy of language. The focus of this paper is on the role of language in building political hegemony through the communication process. Antonio Gramsci, developed the concept of hegemony to explain how certain groups can hold political and cultural control through ideological domination. In the context of general elections, it can be seen how populist language and populist characterizations through the media become political communication strategies in the 2024 elections. Media as the main instrument in creating and strengthening hegemony. The choice of words, rhetoric and narratives become key elements in the formation of images and views in influencing public perception and building consensus on the ideas and values they espouse. This article also finds that the role of political party machines that use symbols and narratives of party programs has a significant impact. By integrating Gramsci's views on language and hegemony into the analysis of political communication strategies for the 2024 elections, this research seeks to provide insight into the complexity of political dynamics from the perspective of the philosophy of language, which can provide a deeper understanding of the dynamics of the 2024 elections. Keywords: Komunikasi Politik, kampanye Pemilu, Antonio Gramsci